Interobserver Reproducibility of Percent Gleason Pattern 4 in Prostatic Adenocarcinoma on Prostate Biopsies. (December 2016) - Sadimin, Evita T.; Khani, Francesca; Diolombi, Mairo; Meliti, Abdelrazak; Epstein, Jonathan I.
Abstract : In the WHO Classification of Tumours of the Urinary System and Male Genital Organs published in 2016, it was officially recommended that the percent of Gleason pattern 4 (GP4) be reported on pathology reports to better reflect the extent in Gleason score 7 tumors. In this study we assessed the reproducibility of reporting GP4 on prostate biopsies. We analyzed prospectively 422 cores containing GP4 from our consult cases over a period of 2.5 months. The percent pattern 4 was assigned to all the cases in 10% increments from 0% to 100% (with the addition of 5%) by 1 of 4 fellows in urological pathology and by the expert urological pathologist. Out of 422 cores, 32% were an exact match and 75% were within ±10% (weighted κ [κW ] value 0.67). Cases were further stratified on the basis of (1) scattered versus clustered GP4 in the background of Gleason pattern 3, (2) continuous versus discontinuous tumor involvement, (3) cribriform/glomeruloid pattern only versus poorly formed/fused pattern versus mixed cribriform and poorly formed/fused pattern, and (4) total tumor involvement of the core (⩽10% vs. >10% of the core). No significant differences were observed in the first 3 variables. However, in cases with ⩽10% involvement of the core, 61% were within ±10% (κW =0.50) compared with cases with >10% involvement of the core, in which 78% were within ±10% (κW =0.70). In summary, we showed that assessment of percent GP4 was relatively reproducible, with substantial agreement within ±10% in cases. However, with <10% involvement of the core, it was more difficult to assess in smaller foci, with only moderate agreement. Given that in a small focus only a few glands of a given pattern can markedly affect the percent GP4, consideration should be given to not recording percent GP4 in small foci of Gleason score 7 tumors on needle biopsy.